METHODOLOGY OF TAFSEER AL-QURTUBI: SOURCES, STYLES AND MANHAJ - Rohman, Abdul; Mubaroka, Barikli; Butlam, Qoree (QiST: Journal of Quran and Tafseer Studies, 2023)
This article examines suorces, styles and the unique method (manhaj) from Tafseer Al-Qurtubi namely of al-Jami' li ahkam al-Quran. The goal of this article is to determine which sources al-Qurtubi used as references, what styles his interpretation, and how the unique method (manhaj khas) he used to carry out his interpretation. This study be written utilizing qualitative approaches based on a literature review or library search. The book of interpretation of al-Jami' li ahkam al-Quran by Al-Qurtubi is the primary source (primary), and the secondary (additional) source is drawn from the books of interpretation of the Qur'an and other pertinent books. The findings show that interpretation Qurtubi's is based on the Qur'an, the Prophet's sunnah, the opinions of the Sahabah and the tabi'in, the history of asbab al-Nuzul, Arabic poetry, qiraat, the opinions of mazhab scholars, and books of interpretation by earlier scholars, including those by Al-Zujaj, Ma'ani al-Quran, Abu Ubaidah, Majaz al-Quran, Al-Qurtubi also quotes from the hadith books, including the nine books (kutub at-tisáh), the Musnads, the Sunan books, and the Maghazi books; tafseer al-Qurtubi style is fiqh interpretation;  and there are ten manhaj used by al-Qurtubi in his commentary.